Quadruplex DNA‐Stabilising Dinuclear Platinum(II) Terpyridine Complexes with Flexible Linkers. Issue 7 (16th December 2015) - Ang, Dale L.; Harper, Benjamin W. J.; Cubo, Leticia; Mendoza, Oscar; Vilar, Ramon; Aldrich‐Wright, Janice
Abstract: Four dinuclear terpyridineplatinum(II) (Pt–terpy) complexes were investigated for interactions with G‐quadruplex DNA (QDNA) and duplex DNA (dsDNA) by synchrotron radiation circular dichroism (SRCD), fluorescent intercalator displacement (FID) assays and fluorescence resonance energy transfer (FRET) melting studies. Additionally, computational docking studies were undertaken to provide insight into potential binding modes for these complexes. The complexes demonstrated the ability to increase the melting temperature of various QDNA motifs by up to 17 °C and maintain this in up to a 600‐fold excess of dsDNA. This study demonstrates that dinuclear Pt–terpy complexes stabilise QDNA and have a high degree of selectivity for QDNA over dsDNA. Abstract : 2 Pts for a win : Dinuclear terpyridine–platinum(II) complexes interact with and stabilise quadruplex DNA (QDNA) and have a high degree of selectivity for QDNA over duplex DNA. Binding interactions were explored via fluorescence resonance energy transfer (FRET), circular dichroism, and computational docking studies.